Oncological outcomes in differentiated thyroid cancer in South East Scotland. Issue 6 (December 2021) - Sawant, R.; FitzGerald, A.; Hey, SY.; Hulse, K.; Hay, A.; Adamson, R.; Nixon, I.J.
Abstract: Background: Differentiated thyroid cancer (DTC) is increasing in incidence but little is known about oncological outcomes for patients treated in the UK. Internationally there is a move toward conservative treatment of DTC. However, this is based on evidence from outside the UK. The aim of this study was to analyse oncological outcomes for a contemporary cohort of patients treated in a UK centre. Methods: Review of 470 consecutive prospectively recorded cases of DTC from the South East of Scotland endocrine MDT 2009–2018. Data on patient, tumour and treatment details as well as recurrence and survival details were extracted from the electronic patient record. Results: Of 470 patients female:male ratio was 3.4:1, median age at presentation was 48 years (range 16–86 years). Overall 193 (41%), 134 (29%), 119 (25%) and 22 (5%) patients were p T1, T2, T3, and p T4 respectively. 385 patients (82%) were pN0, 31 patients (7%) were pN1a and 53 patients (11%) were pN1b. 19 patients (4%) were M1. Of 470 patients 350 (74%) had papillary thyroid carcinoma, 120 patients (26%) had follicular carcinoma. Surgical management was lobectomy, isthumusectomy, total thyroidectomy and lobectomy then completion thyroidectomy in 14%, 1%, 41% and 43% cases respectively. 64% patients received radioactive Iodine (RAI) therapy. With a median follow-up of 70 months (range 4–124 months), 5 years overall survival and disease specific survival were 96.7% and 98.5% respectively. The 5 year local recurrence free survival (LRFS), regional recurrence free survival (RRFS), locoregional recurrence free survival (LRRFS), distant recurrence free survival (DRFS) and any recurrence free survivals were 100%, 95.8%, 95.8%, 98.3% and 95% respectively. Conclusion: Oncological outcomes for patients treated with DTC were excellent, in keeping with experience from international groups, suggesting that a move towards conservative treatment in the UK seems reasonable. Highlights: Differentiated thyroid cancer. Survival analysis. Oncological outcomes.